Predicting the Potential Distribution of Major Malaria Vectors Based on Climate Changes in Sistan and Baluchistan Province, Southeastern Iran - Jalil Nejati; Hassan Vatandoost; Mehdi Zanganeh Baygi; Ahmad Ali Hanafi-Bojd (Tehran University of Medical Sciences, 2022)
Background: Given the significance of climate change and its substantial effects on mosquitoes' habitats, this study was aimed to model the spatial distribution of the main malaria vectors in the south east of Iran. Methods: Several scientific databases between 1980 and 2019 were reviewed to find mosquito species and their spatial information in this area. The archived folders in the center for diseases control and prevention were used to exploit essential data on malaria cases and foci. Three representative concentration pathways (RCP2.6, RCP4.5 and RCP8.5) were chosen to stand for three possible climate scenarios. Finally the potential species distribution of Anopheles stephensi and An. culicifacies s.l. in the 2030s and 2050s horizons were estimated by the Maximum Entropy Model. Results: So far, a total of 39 mosquito species belonging to the family Culicidae have been reported from the study area. In 2019, the total malaria cases have increased by 91% compared to 2015, as well as a sharp rise than 2018 (249%). In that year, 91% of cases were imported from other countries, which caused 40% increase in the new potential foci than in 2018. The Jackknife test demonstrated the annual mean temperature and precipitation of the coldest quarter with the greatest impact on the environmental suitability of the mentioned two species. Conclusion: The effect of climate change on the appearance and recurrence of mosquito-borne diseases has been demonstrated in various studies. Collecting further data and conducting investigation on this issue will improve control management, especially for the malaria vectors.